Microwave-Mediated Extraction of Critical Metals from LED E-Waste - Athanasios B. Bourlinos; Christina Papachristodoulou; Anastasios Markou; Nikolaos Chalmpes; Emmanuel P. Giannelis; Dimitrios P. Gournis; Constantinos E. Salmas; Michael A. Karakassides (ChemEngineering)
This study introduces a microwave-assisted technique for extracting critical minerals from LED electronic waste. The process begins with microwave irradiation, which thermally decomposes the LED’s plastic lens into a brittle, charred residue. During this stage, the LED chip undergoes deflagration—being rapidly ejected from the reflective cavity and becoming embedded within the decomposed lens material. Consequently, the chip is encapsulated in the resulting charred residue. This composite, consisting of the charred lens and the LED chip, can be easily separated from the metallic pins (Fe, Ni, Ag), which remain almost undamaged. Subsequent calcination of the charred material in air exposes the materials making up the LED chip, which contain critical metals (e.g., Ga, As, In, Y, Au). These metals are then extracted through a two-step acid leaching process involving aqua regia followed by hot concentrated hydrochloric acid, yielding them in potentially recoverable forms. The synergistic effect of microwave irradiation and acid treatment achieves an average extraction efficiency of 96% for critical metals. Notably, this approach enables complete and loss-free recovery of the LED chip, offering a practical and efficient solution for LED e-waste recycling.